Estrategia psicopedagógica para promover la autoestima en niños de primaria - Pichucho Alvear, Yuri Nallely (2025)
The present study was conducted at Unidad Educativa La Maná and aimed to design a psychopedagogical strategy to promote self-esteem in fifth-grade students in General Basic Education (EGB). A significant percentage of children were found to have difficulties with self- confidence, social perception, and academic motivation, affecting their emotional well-being and school performance. To address this issue, a mixed-methods design was adopted, combining quantitative and qualitative approaches. The Rosenberg Self-Esteem Scale was applied in a pretest-posttest design with a single group, evaluating self-esteem before and after the intervention. Additionally, direct observations and semi-structured interviews were conducted with teachers and students to analyze changes in children's perceptions and behaviors. The results showed an increase in self-esteem levels following the implementation of the strategy, reflected in greater confidence in their abilities, improved social integration, and a more positive attitude toward learning. However, some students continued to experience insecurity regarding others' opinions and difficulties in emotional regulation. The study concluded that psychopedagogical strategies based on positive reinforcement, cooperative learning, and emotional education contributed to strengthening self-esteem in children. It was recommended to train teachers in emotional reinforcement strategies, promote positive school coexistence, and continuously monitor the impact of the intervention. The research provided a practical tool for educational settings to enhance children's self-esteem and serve as a basis for future interventions in similar contexts